2001
DOI: 10.1128/aac.45.2.460-463.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibodies to Bacterial Superantigens and Their Ability To Inhibit T-Cell Activation and Lethality

Abstract: Bacterial superantigens (BSAgs) cause massive stimulation of the immune system and are associated with various pathologies and diseases. To address the role of antibodies in protection against BSAgs, we screened the sera of 29 human volunteers for antibodies to the SAgs staphylococcal enterotoxin A (SEA), SEB, SEC1, and toxic shock syndrome toxin 1 (TSST-1). Although all volunteers had detectable levels of antibodies against SEB and SEC1, many (9 out of 29 volunteers) lacked detectable antibody to SEA or had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Takei and colleagues [21] showed that IVIG contains anti-SE antibodies that suppress SE-induced T-cell stimulation in vitro. In vivo evidence also indicated that SE-specific antibodies obtained from pooled sera protected mice from a lethal dose of SE [22]. We showed that high concentrations of IgG antibodies against the staphylococcal and streptococcal toxins were present in the IVIG products.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Takei and colleagues [21] showed that IVIG contains anti-SE antibodies that suppress SE-induced T-cell stimulation in vitro. In vivo evidence also indicated that SE-specific antibodies obtained from pooled sera protected mice from a lethal dose of SE [22]. We showed that high concentrations of IgG antibodies against the staphylococcal and streptococcal toxins were present in the IVIG products.…”
Section: Discussionmentioning
confidence: 72%
“…We showed that high concentrations of IgG antibodies against the staphylococcal and streptococcal toxins were present in the IVIG products. These results indicate a high prevalence of antitoxin antibodies in Japanese adults as well as US populations [21,22], and may reflect the virtual absence of KD in adulthood due to widespread immunity. More importantly, we also showed that the administration of immunoglobulin products directly influenced serum IgGantitoxin antibody levels in KD patients.…”
Section: Discussionmentioning
confidence: 87%
“…Synthetic fusion proteins, MHC class II-independent and tumor-specific, have been evaluated successfully. 23,24,[51][52][53][54][55] In summary, the preclinical findings indicate that SEB could be a useful agent for treatment of bladder cancer and that a clinical phase I evaluation appears warranted. …”
Section: Discussionmentioning
confidence: 97%
“…Another issue which needs to be considered is the prevalence of anti-staphylococcal enterotoxins and anti-TSST-1 antibodies in humans. In a study by LeClaire and Bavari, 51 it was shown that detectable levels of antibodies against various staphylococcal enterotoxins (SEA, SEB, SEC1 and TSST-1) can potentially inhibit T-cell activation. This and the fact that the high toxicity of streptococcal and staphylococcal enterotoxins can result in significant human morbidity and mortality lead to the potential use of genetically engineered superantigens.…”
Section: Discussionmentioning
confidence: 99%
“…To assay for neutralization of SPEA activity by serum antibodies, we used the T-lymphocyte proliferation assay [21]. To demonstrate SPEA-specific T-cell inhibition by pooled mouse sera obtained from vaccinated or control mice, sera were incubated (1 h/37°C) with a various doses of SPEA (20 or 200 ng/ml).…”
Section: Serum Antibody and T-cell Stimulation Assaysmentioning
confidence: 99%